Analysis of Financial Performance and Company Value of Conventional Banks and Islamic Banks - Andi Niryanto, Muchamad; Ramadhan, Rizky; Komara, Acep (DINASTI RESEARCH, 2025)
The purpose of this research is to study the difference in financial performance and its impact on firm value between conventional and Islamic banks in Indonesia from 2019 to 2023. With a quantitative approach and descriptive-comparative method, this study investigates various financial performance variables, including capital adequacy ratio (CAR), non-performing debt ratio (NPL), debt-to-deposit ratio (LDR), return on assets (ROA), NIM ratio, and good corporate governance (GCG), and their relationship with firm value, as measured by book price to value (PBV). This data was collected from official publications of the Financial Services Authority (OJK), the Indonesia Stock Exchange (IDX), and bank annual reports.The results showed that in conventional banks, LDR and GCG variables have a significant influence on PBV, while other variables do not have a significant influence. In Islamic banks, on the contrary, ROA and LDR are proven to have a significant influence on PBV, while CAR, NPL, NIM, and GCG have no significant influence. The results suggest that different banking systems have different value determinant structures. Conventional banks focus more on liquidity and governance, while Islamic banks focus more on profitability and efficiency of funds distribution. These results suggest that investors consider various elements in assessing a bank's prospects and valuation, depending on its operational system.